Efficacy and safety of Neemint capsules in an open label single arm trial of patients with gastrointestinal disorders - Vikram, Baburao; Rawal, Neetu; Gupta, Sunil (International Journal of Research in Medical Sciences, 2022)
Anti-inflammatory drugs which are commonly used medication in gastrointestinal (GI) disorder worsen symptoms and increasing impend need of better treatment method for the disease. Neemint capsules composed of polyherbal formulation of neem oil and peppermint oil. We conducted this study to assess the efficacy and safety of Neemint capsules in patients with gastrointestinal disorders including irritable bowel syndrome. We conducted an open label clinical study of 15 patients (mean age, 35.2±14.26 years; 86.6% males) with two or more GI symptoms. Patients were given Neemint capsule of 500 mg (350 mg of neem oil+150 mg of peppermint oil) as per each schedule visit. The primary endpoint was change in gastrointestinal symptom rating scale (GSRS-IBS). Secondary endpoints included monitoring of AE and SAE, IBS-quality of life questionnaire and change in subject’s global assessment of symptoms. The overall GSRS score improvement was found to be 64.23%. The IBS-QOL scores also indicated 57.2% increase in the quality of life of the study subject. The mean global assessment of symptoms (diarrhoea, constipation, abdominal pain, nausea vomiting and bloating) score recorded was 0. All results were significant at p<0.05. In this study we found that Neemint capsules is highly efficacious in the treatment of IBS and GI symptoms and it is also well-tolerated and safe in study subjects (n=15) having complaints of IBS and GI disturbances.